PENGARUH PENGELUARAN PEMERINTAH DAN JUMLAH UANG BEREDAR TERHADAP PRODUK DOMESTIK BRUTI DIMAKASSAR - Rusdi, H Muh; Risnawati, Risnawati (Jurnal Ekonomi Balance, 2016)
Government Lessons to Expand Product Revenues and Money Supply to Gross Domestic Product 2010-2015 in Makassar. The type of data used in this study, ie data related to government expenditures and the amount of funds to the money earned from BPS or related agencies and data used is secondary data, used for magazines, journals, articles and from various previous research results related to the study of this work. The model used to analyze the relationship between the two variables, namely using multiple linear regression analysis. Proven with government investment data, T-count (-2.089) <T-table (4,303) and looks significant to influence X1 and X2 simultaneously to Y is (4,363) <9,55, whereas. In the data the amount of money does not affect the GRDP. From these data it is proven that government expenditures are dominant. Dominant dominant dominant dominant dominant dominant dominant dominant dominant dominant increase in increasing increase in increasing PDRB